Portrait of Social Inequality and Family Crisis in Mirāth by Muhammad Husayn Haykal: Literary Realism Approach - Husnul Khotimah; Misbahus Surur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
As a mimetic cultural artifact, literary conflict frequently encodes the socio-political tensions and ideological fractures of its originating society. Within the framework of literary realism, this study critically interrogates the representation of social inequality and familial disintegration in Muhammad Husayn Haikal's short story